Analisis Faktor Penunjang Keberhasilan Proyek Konstruksi Gedung Buddhi Dharma - Yadi Asso (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Project success is the ultimate goal of every project. The difference in the success factors (Buddhi Dharma Building construction project) projects are due to each project having different influencing factors. Therefore, each party involved must have a certain strategy for the success of the project, namely knowing the most influential factors on the success (success) of the construction implementation. This researcher aims to identify the factors that support the success (Buddhi Dharma Building Construction project) Construction project in the southern Banten city of Tangerang. The research method used is descriptive analysis using a questionnaire with data on construction projects that are currently or have been done. Or the respondents are the main director, project manager, site manager, implementation, technical staff, quantity and quality control. From the returning quisoner, the data was tested using SPSS. There are 30 questionnaires distributed. The response rate is 100%. From the research data there are 4 factors with sub factors / variables. These 4 factors are project management factors, cost, time, quality of work, work safety. The results of the validation test, obtained 4 factors and 7 valid variables. The results of the reliability test, all valid factors are also reliable. From data analysis with SPSS version, 2.4, the most dominant factors on construction costs are: for project management, the plans and schedules used, affecting of project management factors, the most dominant sub-factor is the implementation schedule is not in accordance with schedule, which is of the time, the most dominant sub-factor is the project bidding method, which is 4.7. Equipment factor, the most dominant sub-factor is the monitoring and planning capacity used, which is The results of this researcher are later expected to be taken into consideration for all parties involved in the implementation of construction projects in order to achieve project success.